Sexual risk compensation following voluntary medical male circumcision: Results from a prospective cohort study amongst human immunodeficiency virus-negative adult men in Botswana - Lisa P. Spees; Kathleen E. Wirth; Shreshth Mawandia; Semo Bazghina-werq; Jenny H. Ledikwe (AOSIS, 2020)
Background: Circumcised men may increase sexual risk-taking following voluntary medical male circumcision (VMMC) because of decreased perceptions of risk, which may negate the beneficial impact of VMMC in preventing new human immunodeficiency virus (HIV) infections. Objectives: We evaluated changes in sexual behaviour following VMMC. Method: We conducted a prospective cohort study amongst sexually active, HIV-negative adult men undergoing VMMC in Gaborone, Botswana, during 2013-2015. Risky sexual behaviour, defined as the number of sexual partners in the previous month and ≥ 1 concurrent sexual partnerships during the previous 3 months, was assessed at baseline (prior to VMMC) and 3 months post-VMMC. Change over time was assessed by using inverse probability weighted linear and conditional logistic regression models. Results: We enrolled 523 men; 509 (97%) provided sexual behaviour information at baseline. At 3 months post-VMMC, 368 (72%) completed the follow-up questionnaire. At baseline, the mean (95% confidence interval) number of sexual partners was 1.60 (1.48, 1.65), and 111 (31% of 353 with data) men reported engaging in concurrent partnerships. At 3 months post-VMMC, 70 (23% of 311 with data) reported fewer partners and 19% had more partners. Amongst 111 men with a concurrent partnership at baseline, 52% reported none post-VMMC. Amongst the 242 (69%) without a concurrent partnership at baseline, 19% reported initiating one post-VMMC. After adjustment for loss to follow-up, risky sexual behaviour post-VMMC (measured as mean changes in a number of partners and proportion engaging in concurrency) was similar to baseline levels. Conclusion: We found no evidence of sexual risk compensation in the 3 months following VMMC.